HUBUNGAN KEBIASAAN MEROKOK DAN MENGUNYAH SATU SISI TERHADAP TINGKAT KEPARAHAN PERIODONTITIS - Pitu Wulandari; Aini Haryani Nasution; Irma Ervina; Agnes Nikita Pangaribuan; Gebby Gabrina (B-Dent: Jurnal Kedokteran Gigi Universitas Baiturrahmah, 2022)
Introduction: Periodontitis is an inflammatory condition of the supporting tissues of the teeth caused by one or a group of specific microorganisms that cause progressive periodontal destruction characterized by an increase in probing depth, recession, or both. One of the risk factors for periodontal disease is habitual factors, such as smoking and unilateral chewing. The purpose of this study was to examine the relationship between smoking and unilateral chewing on the severity of periodontitis. Methods: This study was cross-sectional with a retrospective analytical design. The sample used is 67 people. Data was obtained from periodontitis status in 2017-2019 at the Periodontics Clinic of the USU Dental Hospital. Data were analyzed using the Chi-square test with a 95% confidence interval and a 5% significance level (p<0.05). The severity of periodontitis was assessed based on a staging system published by the Academy of Periodontology (AAP) in 2017. Results: The results showed a significant relationship between smoking habits and the severity of periodontitis (p=0.012), as well as a significant relationship between unilateral chewing habits and the severity of periodontitis (p=0.019). Conclusion: The result of this study concluded that is a significant relationship between smoking and unilateral chewing habits on the severity of periodontitis.